Detection of first gammaherpesvirus sequences in Central African bats. (July 2020) - Cameron, K.; Hayes, B.; Olson, S.H.; Smith, B.R.; Pante, J.; Laudisoit, A.; Goldstein, T.; Joly, D.O.; Bagamboula MPassi, R.; Lange, C.E.
Abstract: Herpesviruses have been identified in many species; however, relatively few bat herpesvirus are known, considering the enormous diversity of bats. We used consensus PCR to test bats from the Republic of the Congo and found DNA of two different novel bat herpesviruses. One was detected in a Pipistrellus nanulus, the other in a Triaenops persicus bat and both resemble gammaherpesviruses. On the amino acid level, the amplified sequences differ by 55% from each other, and by 27% and 25% from the next closest known viruses. The findings point towards the diversity of herpesviruses in Central African bats.